Implementation of Electronic Technology Using a Learning Management System as a Medium for ICT-Based Digital Communication Science Learning at the Amari Community Learning Center - Budiyanto, Setiyo; Tomohardjo, Irmulansati; Iman, Fauzi Nur (Journal of Innovation and Community Engagement, 2025)
PKBM Amari, located in South Meruya, West Jakarta, is a non-formal educational institution offering Package A to Package C programs. Despite having qualified educators and active students, the institution faced challenges in digital integration, particularly the absence of a Learning Management System (LMS) and limited digital literacy among teachers and learners. To address these issues, a community empowerment program applies electrical and information technology to develop and implement an LMS-based website as a digital communication learning medium through several key initiatives, namely: (a) developing an LMS-based website, (b) conducting training for teachers and administrative staff, (c) integrating ICT in the learning process, (d) strengthening digital management capacity, (e) establishing sustainable partnerships and networks, and (f) implementing continuous monitoring and evaluation. This program, which supports SDGs 4 (Quality Education) and 8 (Decent Work and Economic Growth), aims to enhance the general quality of education at PKBM Amari through the development of digital skills and the encouragement of responsible technology use. This program generates social and economic benefits in addition to its implementation process. Educators have shown significant improvement in digital literacy, administrative tasks have become more efficient with LMS automation, and students can access learning materials more flexibly. These results show that LMS integration provides real improvements that have a positive impact on social and economic aspects at PKBM Amari.